Դրուագներ հայկական Խաչիսար գիւղի հերոսապատման տարեգրութիւնից - Վիրաբեան, Վանիկ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Во время армяно-татарских столкновений 1915—1906 гг. Хачисар был в составе Елизаветпольского уезда Елизаветпольской губернии. Армяне Хачасара со своей неведанной храбростью и боевой самоотверженностью отличилось во время армяно-татарских стычек․ During the Armenian-Tatar clashes of 1905—1906, Khachisar was part of Elizavetpol district of Elizavetpol province. The Armenians of Khachisar, with their incomparable courage and fighting dedication, distinguished themselves during the Armenian-Tatar clashes.
Keywords: History